Nolph and Gokal's Textbook of Peritoneal Dialysis - Khanna, Ramesh.; Krediet, Raymond T. (Springer US, 2009)
Nolph and Gokal's Text Book of Peritoneal Dialysis, Third Edition, covers advances made in this field for the past 30 years. During the past two decades, the time during which this therapy has been increasingly utilized, this text has continued to be recognized as the major source of the discipline's base knowledge. The evolution of this text to its newest edition parallels the growth of peritoneal dialysis from Continuous Ambulatory Peritoneal Dialysis in the eighties to the current therapy that encompasses manual and automated therapies with full emphasis on adequacy of dialysis dose. Ramesh Khanna, M.D. is Director, Divisionof Nephrology, Department of Medicine, Health Sciences Center, University of Missouri - Columbia, Columbia, MO, USA. Raymond T. Krediet, M.D., Ph.D., is Professor of Nephrology, Renal Unit, Department of Medicine, Academic Medical Center, University of Amsterdam, The Netherlands.